Nothing Like Living with a Family: A Qualitative Study of Subjective Well-Being and its Determinants among Migrant and Local Elderly in Dongguan, China - Liu, Yuxi (Int J Environ Res Public Health, 2019)
Chinese economic development has led to a significant rise in internal migration over the last 20 years, including large numbers of elderly. When elderly Chinese people migrate, they still register their residency to their place of origin and often do not register with the new administrative office at the destination due to the household registration (hukou) system in China. Thus, most of these migrant elderly do not receive full social services, possibly leading to poor subjective well-being. This study aims to qualitatively examine the level of subjective well-being and its determinants among migrants and local elderly in Dongguan City of Guangdong province, one of the most rapid economically developing areas in China. We also present the results of in-depth interviews among 27 elderly, 15 elderly migrants and 12 local elderly living in Dongguan. The results reveal that the overall subjective well-being of the two groups were good. Most migrants believed their well-being had remained stable or even improved over time due to family reunion and a better physical environment. Elderly’s most valuable needs and the main reason of migration is family reunion; however, inadequacy of social support, including community support and government support (e.g., gift during holiday season, free health examination, healthcare expenditure reimbursement), cannot be neglected for maintaining a good level of well-being. The well-being of migrant elderly can be further enhanced by promoting social services and welfare, recreational activities, and enhancing healthcare reimbursement in their new home.